PENGARUH DUKUNGAN KELUARGA, PENGETAHUAN, SIKAP IBU TERHADAP STATUS IMUNISASI BADUTA USIA 12 – 24 BULAN KABUPATEN BELITUNG TIMUR - Herlina, Herlina; Hafizzurachman, Muhammad (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2025)
Immunization-related diseases continue to occur in infants and children in Indonesia. Therefore, the government through the Ministry of Health of the Republic of Indonesia has implemented immunization programs, such as Measles, Tuberculosis, Diphtheria and AFV in children to prevent death. This study aims to examine the influence of family support, maternal knowledge, and maternal attitudes on the immunization status of clowns at the age of 12-24 months in Manggar District, East Belitung Regency. The research was conducted in 2024. This research method uses a quantitative method with a cross sectional design. The primary data collection technique was carried out by interviewing respondents of mothers who have children under five aged 12-24 months. The number of respondents was 87 mothers, who were selected simply randomly from a total population of 619 mothers. The results showed that there was a significant influence of family support, maternal knowledge, and maternal attitudes on the immunization status of clowns at the age of 12-24 months in Manggar District, East Belitung Regency. With statistical evidence, family support contributes significantly to maternal knowledge (f² = 0.758, very high), maternal attitudes (f² = 0.293, medium), and vaccine completeness (f² = 0.306, medium to high). Maternal knowledge plays an important role in improving maternal attitudes (f² = 0.215, medium) and vaccine completeness (f² = 0.226, medium). Based on the results of this study, it is recommended that the clown immunization education program for the age of 12-24 months not only involves the mother, but also the need for support from the family. It is necessary to develop a campaign to form a positive attitude towards immunization. For example, through testimonials from mothers who have fully immunized their children.